Comparison of fine-needle aspiration cytology and ultrasound mammography in diagnosis of clinically palpable breast lump: A retrospective study - Himabindu Narayanapuram; Ramamohanrao Vaitla; Madhurika Karnati (MRIMS Journal of Health Sciences)
Background: Breast lumps have a wide range of causes from physiological adenosis to highly aggressive malignancy. A recent increase in incidence and improved prognosis on early detection of breast cancer necessitates a thorough evaluation of patients presenting with breast symptoms. It is preferred to have the diagnostic methods that are least invasive as well as cost-effective. Objective: The objective of the study was to evaluate the accuracy of fine-needle aspiration cytology (FNAC) and ultrasound breast in the diagnosis of malignancy in a breast lump. Materials and Methods: This was a retrospective observational study, in which patients who had presented with palpable breast masses and were evaluated with ultrasound mammography and FNAC were included in the study. The sensitivity, specificity, predictive values, and diagnostic accuracy of ultrasound mammography and FNAC in diagnosing breast lumps were calculated using the histopathological report as the reference standard test. Results: A total number of patients included in the study were 88. FNAC had reported 27 lumps as malignant, 57 lumps as benign, 2 lumps as phyllodes, and 2 with no opinion possible. Ultrasound breast had reported 56 patients to have benign lumps and 32 patients to have malignant lumps. The sensitivity, specificity, positive and negative predictive values, diagnostic accuracy of FNAC, and ultrasound mammography were 69.23%, 100%, 100%, 78.57%, and 85.54% and 79.48%, 100%, 100%, 84.90%, and 90.48%, respectively. Conclusion: FNAC and ultrasound mammography were 100% specific in diagnosing malignancy in breast lump. The sensitivity of ultrasound appeared to be higher than FNAC. When both diagnostic modalities were combined, there was an increase in the overall sensitivity.